A One‐Dimensional π–d Conjugated Coordination Polymer for Sodium Storage with Catalytic Activity in Negishi Coupling. Issue 41 (3rd September 2019) - Chen, Yuan; Tang, Mi; Wu, Yanchao; Su, Xiaozhi; Li, Xiang; Xu, Shuaifei; Zhuo, Shuming; Ma, Jing; Yuan, Daqiang; Wang, Chengliang; Hu, Wenping
Abstract: π‐d Conjugated coordination polymers (CCPs) have attracted much attention for various applications, although the chemical states and structures of many CCPs are still blurry. Now, a one‐dimensional (1D) π‐d conjugated coordination polymer for high performance sodium‐ion batteries is presented. The chemical states of the obtained coordination polymer are clearly revealed. The electrochemical process undergoes a three‐electron reaction and the structure transforms from C=N double bonds and Ni II to C−N single bonds and Ni I, respectively. Our unintentional experiments provided visual confirmation of Ni I . The existence of Ni I was further corroborated by its X‐ray absorption near‐edge structure (XANES) and its catalytic activity in Negishi cross‐coupling. Abstract : A conjugated coordination polymer for sodium‐ion batteries is presented. The chemical states of the obtained coordination polymer are clearly revealed, indicating that the electrochemical process undergoes a three‐electron reaction and the structure transforms from C=N double bonds and Ni II to C−N single bonds and Ni I, respectively. Furthermore, the discharged electrodes (Ni I ) can be used as quasi‐single‐atom catalyst in Negishi cross‐coupling.